Juridical Analysis of Consumer Protection against Buying and Selling Fraud in the Market Place - Bintarawati, Fenny (Universitas Islam Negeri Walisongo Semarang, 2022)
The rise of fraud cases in the marketplace shows that the position of consumers when transacting online is weak. However, this does not mean that sellers are free to sell their goods without complying with applicable regulations. the problem is this research is presented on how to protect consumers in the marketplace based on Law Number 11 of 2008 concerning Information and Electronic Transactions and how aspects of legal protection and accountability of business actors in the marketplace are presented. The method in this research uses normative legal research. This method is guided by the laws and regulations in Indonesia. This research find that the legal principle remains that every person who causes a loss to others must bear the responsibility for what he has done. So in this case the consumer can file a claim in the form of compensation to the business actor. The compensation according to Article 19 paragraph 2 of the Information and Electronic Transactions includes the return of a sum of money, the replacement of goods or services of an equivalent kind, health care, and the provision of compensation in accordance with the provisions of the legislation. When buying and selling online or online in the marketplace, business actors must understand and understand the rights and obligations of each party, be it the seller or the buyer. In addition, business actors must also understand the problem solving mechanisms available in the electronic transaction management system or what is meant in this case is the marketplace. Maraknya kasus penipuan yang ada pada market place memperlihatkan bahwa kedudukan konsumen saat bertransaksi online sifatnya lemah, meskipun demikian bukan berarti penjual bebas menjual barang mereka tanpa mematuhi regulasi yang berlaku. Berdasarkan latar belakang masalah dipaparkan rumusan masalah bagaimana perlindungan konsumen dalam marketplace berdasarkan Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik serta bagaimana aspek perlindungan hukum dan pertanggungjawaban pelaku usaha dalam marketplace. Metode penelitian dalam penelitian ini menggunakan jenis penelitian hukum normatif, yakni penelitian yang berpedoman pada peraturan perundangan di Indonesia. Dengan hasil penelitian bahwa tetap berlakunya prinsip hukum bahwa setiap orang yang melakukan suatu akibat kerugian bagi orang lain, harus memikul tanggung jawab yang diperbuatnya. Maka dalam hal ini konsumen dapat mengajukan tuntutan berupa kompensasi/ ganti rugi kepada pelaku usaha. Kompensasi tersebut menurut Pasal 19 ayat 2 UUPK meliputi pengembalian sejumlah uang, penggantian barang atau jasa sejenis yang setara, perawatan kesehatan, dan pemberian santunan sesuai ketentuan perundang-undangan. Maka bisa disimpulkan pelaku usaha saat berjual beli secara daring atau online di marketplace harus mengerti dan paham mengenai hak dan juga kewajiban tiap pihak baik itu penjual ataupun pembeli, sekaligus paham terkait mekanisme penyelesaian masalah yang tersedia pada sistem penyelenggara transaksi elektronik atau yang dimaksudkan dalam hal ini ialah marketplace.